Best full paper award for 2017 - Kyriakidis, Phaedon (My University, 2026)
Best full paper award for 2017 at the international conference of AGILE: Association of Geographic Information Laboratories in Europe. Best Full Paper Beyond Pairs: Generalizing the Geo-dipole for Quantifying Spatial Patterns in Geographic Fields Rui Zhu, Phaedon Kyriakidis and Krzysztof Janowicz
Keywords: Sciences